THE CREATION OF RADEN ADJENG KARTINI’S PUTUT DHAPUR KERIS - Saputri, Puput; Yuwono, Basuki Teguh (ARTISTIC : International Journal of Creation and Innovation, 2022)
Raden Adjeng Kartini, an Indonesian national hero from Jepara, Raden Adjeng Kartini, is an interesting inspiration for keris art. This creation seeks to realize the keris putut’s work with Raden Adjeng Kartini's dhapur as a form of respect and to imitate her character. The putut keris is made using a forging (tempa) technique and the primary ingredients of iron, nickel, and steel. The method of creation used is exploration, design, and embodiment. Meanwhile, the conceptual basis consists of greget, guwaya, and wangun. This creation results in three keris: the Putut Dhapur Emansipasi Raden Adjeng Kartini Keris, the Putut Dhapur Madhurya Raden Adjeng Kartini Keris, and the Putut Dhapur Anggit Raden Adjeng Kartini Keris. Each keris has a meaning related to Raden Adjeng Kartini’s character.